The profile of patients with haemophilia managed at a haemophilia treatment centre in Pretoria, Gauteng - Lethukuthula Mafisa; Abegail N. Dlova; Vanessa Moodley (South African Family Practice)
Background: Haemophilia A and B are X-linked recessive bleeding disorders resulting from a deficiency of factors VIII and IX, respectively. Early diagnosis and a comprehensive approach to management is mandatory. This study aimed to describe the profile of patients with haemophilia (PWH) managed at Dr George Mukhari Academic Hospital (DGMAH) with the view to identify potential areas to improve haemophilia care.